Construction of Baloch Ethnic Identity In Music on Social Media Platform YouTube - Baloch, Marvi (2024)
This study investigates the construction of Baloch ethnic identity through the social media platform YouTube. The topic of ethnic minorities and their suppression has been extensively researched but there is little research on the issue of ethnic minorities in Pakistan. Secondly, suppressed ethnic minorities also use music as a medium to represent their issues (e.g. Fadel, 2022; Clough, 2018), however, there is no research available on the use of the social media platform YouTube to represent Baloch ethnic groups. The present study probes the question of how Baloch musicians use music to construct their ethnic identity and ethnic conflict through the social media platform YouTube. The data set consists of eight music videos, which are available on YouTube. The data was collected through a purposive sampling technique. To analyze the data, the thematic analysis method was used. The data produced two main themes along with sub-themes. The analysis of data showed that YouTube provides a medium for Baloch artists to present the cultural, political, and economic situation of Baluchistan. The results of state suppression against minority groups are the cultivation of rebellious sentiments and voicing against the enforced disappearance. Music is playing a peaceful way and catalyst to convey the grievances of the Baloch people and remind their people about the atrocities and courage. Moreover, cultural identity components like the Baloch code of conduct are emphasized in the songs. Music helps musicians to navigate their cultural laws. This study will help to understand the significance of cultural creativity in promoting unity, creating awareness, and addressing systematic inequalities